Evaluation of Nursing Performance Concerning Nasogastric Tube in Neonatal Intensive Care Unit at al-Batool Teaching Hospital in Baqubah City - Nayef, aqeel; Neamah, Mahdi (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: The study aim to evaluate nursing performance during nasogastric tube feeding in neonatal intensive care unit. Methodology: A descriptive study was carried out in Neonatal Intensive Care Unit at al–Batool Teaching Hospital, for the purpose of evaluate of quality of nursing performance for premature baby during nasogastric tube feeding in neonatal intensive care unit. The study consumed the period from 4th of December 2017 to the 24nd of April 2018, Non-probability purposive sample of (25) nurses working in the neonatal intensive care unit. The data were collected through the use of Observational instrument which consist of socio-demographic characteristics, quality of nursing care. Results: The study shows that the majority of participants was female with age (20-29) years with diploma and more half was married with somewhat sufficient of monthly income, years of experience in nursing and neonatal intensive care unit were, quality of care before, during, and after at fair level Recommendations: Advanced video programs, specific meetings, programs, workshops, training activities and seminars, and Booklet are should be provided for nurses on how to use global standards to placement of the nasogastric feeding tube in NICU. And it's recommended to provide the necessary advanced supplies and equipment for nasogastric feeding tube procedure.